Surgical Diagnosis and Treatment of Primary Retroperitoneal Liposarcoma - Chen, Jie; Hang, Ying; Gao, Qi; Huang, Xinyu (Frontiers in Surgery, 2021)
Background: Primary retroperitoneal liposarcoma (PRPLS) is the most common soft tissue sarcoma of the retroperitoneum. The recurrence rate is high and the overall survival (OS) is short. Methods: A retrospective review of 51 patients with PRPLS, treated between September 1, 2009 and November 30, 2020, was conducted to evaluate the clinical results of PRPLS resection. Patient demographics, histopathologic subtypes, overall survival (OS), progression-free survival (PFS), disease recurrence rate, and tumor stage were reviewed and analyzed. Univariate analysis was done to identify factors potentially affecting OS and PFS of PRPLS patients. Multivariate Cox proportional hazards analysis was used to evaluate the impact of various clinicopathological factors on OS and PFS of PRPLS patients. Results: Fifty-one PRPLS patients (28 Males, 23 Females; mean age 56.25 years) were evaluated. There was no significant effect of age, gender, contiguous organ resection, degree of differentiation and tumor size on the OS and PFS of the patients. In the univariate analysis, negative surgical margin and early tumor stage were significantly correlated with OS and PFS (all P < 0.001). In the multivariate analysis, tumor stage [hazard ratio (HR)=1.177, P=0.001] was identified as independent predictors of poor progression-free survival. Surgical margins [HR=4.0674 P=0.038] and tumor stage [HR=1.167 P=0.001] were found to be an independent predictor of poor overall survival in the multivariate analysis. Conclusion: Negative surgical margin was a prognostic factor of OS, which could prolong the postoperative survival time of PRPLS. Tumor stage was a prognostic factor for OS and PFS, which inﬂuenced the survival of PRPLS. Earlier tumor stages of PRPLS were associated with significantly better outcomes.